2020
DOI: 10.1021/acsami.9b21261
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Water as New Binding Sites for the Separation of Light Hydrocarbons in Metal–Organic Frameworks with Open Metal Sites

Abstract: Metal−organic frameworks with open metal sites are promising materials for gas separations. Particularly, the M 2 (dobdc) (dobdc 4− = 2,5dioxidobenzenedicarboxylate, M 2+ = Co 2+ , Mn 2+ , Fe 2+ , ...) framework has been the Drosophila of this research field and has delivered groundbreaking results in terms of sorption selectivity. However, many studies focus on perfect two-component mixtures and use theoretical models, e.g., the ideal adsorbed solution theory, to calculate selectivities. Within this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…They observed increases in CO 2 /N 2 selectivity in the presence of H 2 O, but simulations performed using MOFs preloaded with H 2 O showed decreases in CO 2 working capacities. , Rogacka et al also used molecular screening and surveyed 2932 MOFs and found 13 materials that were selective for CO 2 in the presence of water and, in many cases, the selectivity either increased, decreased, or remained unchanged depending on the amount of water present . When examining water adsorption on MOF-74, Vervoorts et al found that water adsorbed onto the metal centers in the MOF and provided a new binding site for hydrocarbon adsorbates . In addition to examining MOFs, covalent organic frameworks have also been examined with CO 2 selectivity in the presence of water …”
Section: Introductionmentioning
confidence: 99%
“…They observed increases in CO 2 /N 2 selectivity in the presence of H 2 O, but simulations performed using MOFs preloaded with H 2 O showed decreases in CO 2 working capacities. , Rogacka et al also used molecular screening and surveyed 2932 MOFs and found 13 materials that were selective for CO 2 in the presence of water and, in many cases, the selectivity either increased, decreased, or remained unchanged depending on the amount of water present . When examining water adsorption on MOF-74, Vervoorts et al found that water adsorbed onto the metal centers in the MOF and provided a new binding site for hydrocarbon adsorbates . In addition to examining MOFs, covalent organic frameworks have also been examined with CO 2 selectivity in the presence of water …”
Section: Introductionmentioning
confidence: 99%
“…Note that this slight shape sieving may not achieve an ideal sieving effect, but it is important to influence the diffusion behavior of molecules. A deep insight into the Hirshfeld surface (Figure f) is that it can be observed that a highly attractive negative electrostatic potential mapped with −0.05 au (red) was clearly distributed in the pore channel, suggesting the enriched pore polarity, which favored the binding interaction with the molecule that had a larger dipole moment. , In brief, due to decent molecule dimensions and the large dipole moment of C 3 H 6 , it is expected to form strong interactions with the polar pore surface and will effortlessly diffuse into the adaptive pore channel.…”
Section: Resultsmentioning
confidence: 99%
“…In situ spectroscopies, crystallographic experiments, and modeling demonstrated that two C 3 H 6 molecules confined in one unit cell were grasped through multiple binding interaction including van der Waals effects, hydrogen bonding, and intraintermolecular interaction. Molecular dynamics showed that 1 possessed a higher diffusion selectivity of 19…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Additionally, the porosity of MOFs allows incorporation of various guest molecules into their voids, which can influence the properties of the materials. [21] The chemical and structural versatility of MOFs, as well as their potentially high surface areas and porosity, have facilitated their application as catalysts, [22][23][24] materials for gas storage [25] and separation, [26,27] as chemical sensors, [28,29] as photosensitisers for photodynamic therapy [30] and other applications. [31] The ability to incorporate photosensitising ligands (e.g.…”
Section: Introductionmentioning
confidence: 99%